KEMAMPUAN MANAJEMEN KELAS GURU: PENELITIAN TINDAKAN DI SEKOLAH DASAR DENGAN SES RENDAH - Helsa, Helsa; Hendriati, Agustina (Faculty of Psychology, Diponegoro University, 2017)
This is an action research that aims to identify and improve classroom management skill of six homeroom teachers in a low socio-economic elementary school. Classroom management skill is defined as teacher’s ability to create and maintain a learning environment that conducive to learning. The classroom management skill is measured using an observation-based rating scales and semi-structured interviews. The findings showed that classroom management skills were lacking among the majority of participants because they did not have sufficient knowledge about classroom management and did not understand their class’ needs. After two periods of intervention, the participants’ classroom management skill is improved. It was revealed that individual coaching is more effective than training method in improving classroom management skill. Furthermore, educational background and previous professional experience influenced participants’ classroom management skill. However, participants with the relevant educational background do not automatically master classroom management skill, unless supported with professional experience.